The Influence of Work Environment And Work Motivation on the Performance of Employees in the Health Service, Population Control and Family Planning: JEL Classification: K11, K12, K24, D18, O34 - Sarinah, Sarinah; Suyuthi , Nurmadhani Fitri; Insan , Andi Nur (Journal La Bisecoman, 2025)
work motivation on employee performance at the Nunukan Regency Population Control and Family Planning Health Service. This research uses quantitative methods by collecting data through questionnaires distributed to employees at the agency. The collected data was then analyzed using statistical techniques to test the relationship between work environment variables, work motivation and employee performance. The research results show that less conducive work environments, such as hot air temperatures and room cleanliness, do not have a significant influence on employee performance. This indicates that although the work environment can influence comfort, its impact on work productivity is not significant. On the other hand, work motivation is proven to have a positive and significant influence on employee performance, with a high level of motivation playing an important role in increasing dedication and task achievement. Overall, both the work environment and work motivation, both individually and collectively, have a significant influence on employee performance. Based on the results of this research, motivation factors are important in improving employee performance, while the work environment also needs to be considered to create a more conducive work atmosphere. This research suggests that agencies should focus more on developing programs that can increase work motivation, such as providing incentives and rewards, as well as improving the physical conditions of the work environment to increase employee comfort.